Visceral adiposity, inflammation, and hippocampal function in obesity. (1st March 2022) - Stranahan, Alexis M.
Abstract: The 'apple-shaped' anatomical pattern that accompanies visceral adiposity increases risk for multiple chronic diseases, including conditions that impact the brain, such as diabetes and hypertension. However, distinguishing between the consequences of visceral obesity, as opposed to visceral adiposity-associated metabolic and cardiovascular pathologies, presents certain challenges. This review summarizes current literature on relationships between adipose tissue distribution and cognition in preclinical models and highlights unanswered questions surrounding the potential role of tissue- and cell type-specific insulin resistance in these effects. While gaps in knowledge persist related to insulin insensitivity and cognitive impairment in obesity, several recent studies suggest that cells of the neurovascular unit contribute to hippocampal synaptic dysfunction, and this review interprets those findings in the context of progressive metabolic dysfunction in the CNS. Signalling between cerebrovascular endothelial cells, astrocytes, microglia, and neurons has been linked with memory deficits in visceral obesity, and this article describes the cellular changes in each of these populations with respect to their role in amplification or diminution of peripheral signals. The picture emerging from these studies, while incomplete, implicates pro-inflammatory cytokines, insulin resistance, and hyperglycemia in various stages of obesity-induced hippocampal dysfunction. As in the parable of the five blind wanderers holding different parts of an elephant, considerable work remains in order to assemble a model for the underlying mechanisms linking visceral adiposity with age-related cognitive decline. This article is part of the special Issue on 'Cross Talk between Periphery and the Brain'. Highlights: Visceral adiposity is a risk factor for diabetes and for age-related cognitive decline Insulin resistance develops hetereogeneously in different cell types and tissues Tissue-specific insulin resistance perturbs hepatokines, myokines, and adipokines known to regulate cognition Dysfunctional interactions at the blood-brain and blood-cerebrospinal fluid barriers also contribute to neuroinflammation and cognitive deficits in visceral obesity